1997
DOI: 10.1037/0022-3514.73.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Coping with moral commitment to long-distance dating relationships.

Abstract: The uncertainty of relationship transitions should elicit more elaborate cognitive processing about one's relationship. As a result, reports of a type of relationship commitment distinctive from satisfaction-moral commitment-might be obtained from those about to begin long distance relationships. Students assessed prior to the academic year reported 2 types of commitment: moral and enthusiastic. Moral commitment was highly correlated with the meaning of the relationship and investment in the relationship, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 38 publications
(51 reference statements)
1
56
0
Order By: Relevance
“…The importance of such contact, however, may diminish in LD friendships, particularly for young adults who have an array of means for communicating. Lydon, Pierce, and O'Regan (1997) detected no significant difference in level of commitment between GC and LD romantic relationships; however, moral commitment was predictive of continuation during the transition to LD, whereas enthusiastic commitment, which related to relational satisfaction, was not. Overall, the evidence seems to suggest that proximity positively relates to commitment: H1: GC friends report a higher level of commitment than LD friends.…”
Section: Previous Research Examining Commitment In Ld Relationshipsmentioning
confidence: 48%
“…The importance of such contact, however, may diminish in LD friendships, particularly for young adults who have an array of means for communicating. Lydon, Pierce, and O'Regan (1997) detected no significant difference in level of commitment between GC and LD romantic relationships; however, moral commitment was predictive of continuation during the transition to LD, whereas enthusiastic commitment, which related to relational satisfaction, was not. Overall, the evidence seems to suggest that proximity positively relates to commitment: H1: GC friends report a higher level of commitment than LD friends.…”
Section: Previous Research Examining Commitment In Ld Relationshipsmentioning
confidence: 48%
“…There are mixed findings from past research on whether moral commitment has an impact on psychological well-being. One study showed that moral commitment was uncorrelated with relationship satisfaction, but was positively correlated with negative affect (Lydon et al 1997). Another study showed that moral commitment was found to be positively associated with life satisfaction among husbands, but not wives .…”
Section: Relationship Commitment and Relationship Satisfactionmentioning
confidence: 96%
“…Psychological distance is defined as the degree to which an object is perceived to be tangible or immediately present in terms of the here-and-now (Liberman, Trope, and Stephan 2007;Trope and Liberman 2010). The international and interpersonal relationship literatures (e.g., Chang, Polachek, and Robst 2004;Conway and Swift 2000;Lyndon, Pierce, and O'Regan 1997) lend support to the distinction between physical and psychological dimensions of distance, and further find that physical distance explains between 44% and 73% of the variance in psychological distance (Briggs 1973;Coshall 1985;Phipps 1979). Thus, one implication of CLT is that, ceteris paribus, a hybrid retailer with a local store should be perceived as more psychologically proximal than a hybrid retailer with a physically distant store, and that any effects of physical distance on consumer judgment should be at least partly explained by psychological distance.…”
Section: Construal-level Theory and Different Facets Of Psychologicalmentioning
confidence: 99%